Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)
Female Weddell seals ( Leptonychotes weddellii ) display a mixed capital-income breeding strategy, losing up to 40% of their body mass between birthing and weaning their pups. How and when they regain energy stores, however, remains to be fully explored. To better understand the foraging by lactating Weddell seals, we fitted time-depth recorders and head-mounted cameras on 26 seals in Erebus Bay, Ross Sea, for ~ 5 days in November and December 2018 and 2019. We aimed to (1) identify prey species and foraging depth and (2) investigate relationships between seal physiology and demographics and probability of foraging. We recorded 2782 dives, 903 of which were > 50 m, maximum depth was 449.3 m and maximum duration was 31.1 min. Pup age likely contributes to the probability of a lactating Weddell seal foraging (Est. = 1.21 (SD = 0.61), z = 1.97, p = 0.0484). Among 846 prey encounters, the most frequent prey items were crustaceans (46.2%) and Antarctic silverfish ( Pleuragramma antarcticum , 19.0%); two encounters were observed with juvenile Antarctic toothfish ( Dissostichus mawsoni , 0.2%). We identified substantial variability in foraging behaviour, individually and between locations, and found that lactating seals target many species and some may specialise on certain prey groups.